Perlindungan Hukum Terhadap Anak Pelaku Pencabulan Anak Berdasarkan Asas Keadilan - Perdana, Ega Surya; Huda, Miftakhul (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes the implementation of legal protection for children in conflict with the law (ABH) as perpetrators of child molestation, particularly in terms of its compliance with the principles of justice in Indonesia. This study uses a normative-empirical method, focusing on an analysis of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) and court ruling practices. The results indicate that the Indonesian legal framework strives to balance restorative justice (protection and rehabilitation of child offenders) with demands for retributive justice (criminal accountability). The SPPA Law prioritizes the best interests of children through diversion and non-imprisonment sanctions. However, in cases of child molestation, this goal is legally hampered by the threat of criminal penalties exceeding the 7-year prison sentence required for diversion (Article 7 of the SPPA Law). This situation creates a justice dilemma. Justice for victims (which demands severe accountability) often conflicts with the protection of the rights of child offenders. Although diversion is formally difficult to implement, law enforcement officials often use discretion and the results of community research (Litmas) to apply restorative justice principles during trials. However, this practice is often not balanced with adequate fulfillment of victims' rights, such as restitution and rehabilitation, resulting in substantive justice not being achieved holistically. The conclusion of this study confirms that legal protection for child molesters does not fully align with the principle of balanced justice due to normative barriers and the weak integration of victim recovery into the restorative process. It is recommended that the limits of the criminal penalty for diversion in the Child Protection and Protection Act (UU SPPA) be revised and the mandatory restitution mechanism strengthened for victims to achieve complete justice.